Psychometric evaluation of self‐report measures of binge‐eating symptoms and related psychopathology: A systematic review of the literature. Issue 2 (27th August 2015) - Burton, Amy L.; Abbott, Maree J.; Modini, Matthew; Touyz, Stephen
ABSTRACT: Objective: Binge eating is a symptom common to bulimia nervosa, anorexia nervosa (binge/purge subtype), and binge eating disorder. There are many self‐report measures available to aid the assessment of eating disorders symptoms, but there has not yet been a systematic review of the literature to identify the most valid and reliable measures for use in assessment and treatment of binge eating. Method: A systematic review of the psychometric properties of self‐report measures that assess binge eating symptoms and psychopathology was conducted. Two independent raters assessed the psychometric properties of each measure using a standardized quality analysis tool. Results: Of the 2, 927 studies identified, 72 studies met the inclusion criteria and described the psychometric properties of 29 different self‐report measures, and nine specific subscales within these. Results from the quality analysis tool utilized in this study indicated that none of the included measures currently meet all nine criteria of adequate psychometric properties. Discussion: Most of the included measures had evidence for some adequate psychometric properties. Two measures received six out of nine positive ratings for the assessed psychometric properties, the BITE and the BULIT‐R, and thus appear to be the measures with the most evidence of their validity and reliability. Overall, our findings implicate a need for further investigation of the psychometric properties of the available self‐report questionnaires in this field. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:125–142).